"Урядова записка про потреби Києва" як джерело для вивчення діяльності органів міського врядування - Глизь, Ю. (Український історичний збірник, 2018)
Подається «Записка о нуждах г. Киева» київського міського голови
Густава-Адольф Ейсмана, дані якої лягли в основу висновків ревізії сенатора
О.О. Половцева. У ній були зауважені апатичність гласних у роботі думи та
управи, зловживання довіреностями на виборах та окремо виділена проблема
проживання євреїв у Києві. Submitted «The government note about the needs of Kyiv» writted by Kiev city
mayor Gustav-Adolf Eysman. Senator thought highly of him because he served this
post one cadence, was the active city leader, knew local conditions and practices of
Western governments, which missing high-Petersburg official. There were comments
the lethargy glasnyh in the City council and board, abuse of power of attorney in the
elections separately and highlighted the problem of jews living in Kiev. Noted that the
City Regulations 1892 assumed a number of restrictions on Jews: the number of
glasnyh in their chosen decreased from 1/3 to 1/5, unlike City Regulations 1870. Most
importantly, the City Regulation in 1892 it was banning Jews hold office glasnyh or
control commission City council only in Kiev, while in other cities it is allowed. The
government note prepared for Senator Alexander Polovtsev, contains a deep analysis
of the situation in Kiev city government and major proposals to improve it. Most of
them were taken into account and reflected in City regulations 1892. In particular, the
initiative of the Kyiv City Council, which since 1880 has transferred the election of the
third category of voters in the district principle fully justified itself, and therefore the
City Regulation 1892 election categorical principle was replaced by the district,
which accelerated the process of voting.